Mobility of the line : art, architecture, design - Wingham, Ivana (Basel, SZ. : Birkhauser, 2013)
The line is the constitutive element of every drawing and forms the core element of any design - for art, architecture, urban design or design in general. It resists reduction to simple linearity, but rather takes on complex and dynamic forms that attract the viewer in various ways, both consciously and suggestively. Whether analogue or digital, line is mobile as the forces, movements and effects that line produce are different for each type of line: straight, meandering, interrupted or even invisible. The book is a stimulating celebration of the manifold aspects of line, using unique examples from architecture, design and art, combining interviews with designers and essays by various authors.
Includes bibliographical references and index.
Keywords: Line (Art).; Architectural drawing; Design -- Technique